Integrated management of rice sheath blight under field condition - and JANKI KANDHARI, M. SURULIRAJAN (Indian Phytopathology, 2005)
The present study was undertaken to assess the disease severity, percent disease incidence (PDI) and yield parameters (grain yield, straw yield and 1000 grain weight) against sheath blight of rice through different combinations of treatments in the field during 1999 and 2000. Out of sixteen treatments, Trichoderma viride (TV. 3235) + carbendazim 50 WP (0.1%) spray along with soil amendments (FYM 1% + Saw dust 1%) showed the maximum reduction in sheath blight severity, percent disease incidence and higher grain yield over the control.